Validation of android-based mobile application for retrieving network signal level - Kehinde A. Adeniji; Nazmat T. Surajudeen-Bakinde; Olusegun O. Omitola; Adedayo Ajibade (Indonesian Journal of Electrical Engineering and Computer Science, 2021)
In recent years, the evolvement of mobile devices which perform sophisticated functions have been on the rise. Mobile applications which solved engineering challenges are now available due to the high computational capabilities, large random access memory and storage location of the mobile devices. An Android application called signal detect, which measures network signal strength value from 2G-4G received on an android mobile device has been developed using android app development environment called Android studio. Validation becomes necessary because different readings were obtained on smartphones with different specifications. Two validation techniques were used to validate the data obtained. To know the efficiency of the application; a field strength meter was used to compare the readings received on the mobile device with the meter. It was observed that there is a time lag on the received values of the mobile device to the field strength meter. Therefore, a moving average technique was used to correlate the two data which increased the correlation coefficient to about 0.85.